Management of Slums in the Kotaku Program with Sustainable Urban Governance in Batam City - Murtiono, Hendro; Gunawan, IGN Anom; Rinoa, Livvy (Universitas Ibn Khaldun Bogor, 2024)
The impact of urbanization is closely related to urban settlement problems. One of the government's efforts to solve the problem of housing needs for low-income people in densely populated urban areas is to build vertical housing or flats. The City Without Slums Program (KOTAKU) is one of the strategic efforts of the Directorate General of Cipta Karya, Ministry of Public Works and Public Housing (PUPR) to accelerate the handling of slums in urban areas and support the